The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1152/jn.00850.2013
|View full text |Cite
|
Sign up to set email alerts
|

Organization and trade-off of spectro-temporal tuning properties of duration-tuned neurons in the mammalian inferior colliculus

Abstract: Neurons throughout the mammalian central auditory pathway respond selectively to stimulus frequency and amplitude, and some are also selective for stimulus duration. First found in the auditory midbrain or inferior colliculus (IC), these duration-tuned neurons (DTNs) provide a potential neural mechanism for encoding temporal features of sound. In this study, we investigated how having an additional neural response filter, one selective to the duration of an auditory stimulus, influences frequency tuning and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 87 publications
4
9
1
Order By: Relevance
“…5A; R 2 ϭ 0.639, P Ͻ Ͻ 0.001). This finding demonstrates that DTNs are also tonotopically organized, thus replicating previous findings about duration tuning in the IC (Haplea et al 1994;Jen and Wu 2006;Morrison et al 2014;Pinheiro et al 1991;Sayegh et al 2012). Most of the DTNs in our sample (97.6%) had BEFs that fell between 20 and 70 kHz.…”
Section: Tonotopic Organization Of Dtns In Icsupporting
confidence: 91%
See 1 more Smart Citation
“…5A; R 2 ϭ 0.639, P Ͻ Ͻ 0.001). This finding demonstrates that DTNs are also tonotopically organized, thus replicating previous findings about duration tuning in the IC (Haplea et al 1994;Jen and Wu 2006;Morrison et al 2014;Pinheiro et al 1991;Sayegh et al 2012). Most of the DTNs in our sample (97.6%) had BEFs that fell between 20 and 70 kHz.…”
Section: Tonotopic Organization Of Dtns In Icsupporting
confidence: 91%
“…The spectral tuning of auditory DTNs is of particular interest given that spectral and temporal features of biological sounds are often comodulated (Heil et al 1992;Suga 1984). Recent studies have shown that DTNs in the mammalian inferior colliculus (IC) show a trade-off in their spectro-temporal response resolutions in a manner analogous to resonant electrical filters (Morrison et al 2014). Moreover, the frequency selectivity of a DTN can change when it is stimulated with sound pulses that are varied in duration (Wu and Jen 2008a).…”
mentioning
confidence: 99%
“…This result is also consistent with the finding that some DTNs are sensitive to binaural interaural level difference and interaural time difference cues important for sound localization ). Furthermore, a study on the interaction between frequency and duration tuning demonstrated that DTNs exhibited two patterns of spectro-temporal sensitivity and spatial organization within the IC: cells with sharp frequency tuning and broad duration tuning were located in the dorsal IC, and cells with wide spectral tuning and narrow temporal tuning were located in the ventral IC (Morrison et al 2014). Bats systematically vary the duration of their echolocation calls while foraging, and there are a number of reasons why it would be helpful for the bat to "know" when an external signal of a specific frequency (or bandwidth), amplitude (intensity), and duration was received by each ear.…”
Section: Discussionmentioning
confidence: 99%
“…In our dataset DTNs varied in their response characteristics from having very narrow (responding to only 1 or 2 durations) to quite broad (responding to a wide range of durations) temporal tuning curves (see also Morrison et al 2014). Therefore, the perfor-mance of a decoder using randomly selected DTNs as inputs would be highly dependent on the particular subset of cells chosen.…”
Section: Decoding Stimulus Durationmentioning
confidence: 99%
“…Detailed explanations of animal care and institutional approval, surgical preparation and anaesthesia, stimulus generation, and neural recording procedures have been published [21,22].…”
Section: Methodsmentioning
confidence: 99%